European Bioanalysis Forum recommendation on method establishment and bioanalysis of biomarkers in support of drug development. (August 2012) - Timmerman, Philip; Herling, Christian; Stoellner, Daniela; Jaitner, Birgit; Pihl, Susanne; Elsby, Karen; Henderson, Neil; Barroso, Begona; Fischmann, Stephanie; Companjen, Arjen; Versteilen, Amanda; Bates, Stewart; et al.
Biomarkers have become increasingly important in drug development and many bioanalysts are getting involved. Consequently, different views on how to approach the bioanalysis of biomarkers have been published or are being developed. The European Bioanalysis Forum has intensively discussed this topic since 2010 and is ready with their recommendation on method establishment and bioanalysis of biomarkers. Acknowledging that the challenges step outside the bioanalytical laboratory is a cornerstone of our recommendation. The importance of integrating all scientific aspects, from purely analytical aspects, all the way to understanding the biology and effects of the biomarker, prior to embarking on method establishment or sample analysis, cannot be underestimated. Close and iterative interactions with the teams requesting the data is imperative to develop a bioanalytical strategy that combines science, analytical performance and regulations. The European Bioanalysis Forum developed a straightforward decision tree to help the scientific community in developing a bioanalytical strategy for any biomarker in drug development.